Age-Based Health Insurance Coverage Policies and Mental Health - Yiran Han; Baris Yörük (Institute of Labor Economics (IZA), 2022)
More than 18 percent of U.S. adults met the diagnostic criteria for a mental illness. Yet, many who could benefit from mental health care do not receive any treatment, mostly due to the inability to pay for care or lack of health insurance coverage. How does a sudden change in health insurance coverage status affect psychological well-being and mental health? We explore this question using age-based health insurance coverage policies in the United States as natural experiments. We provide evidence that losing health insurance coverage at age 26 due to aging out from dependent coverage is associated with a statistically significant deterioration in certain indicators of mental health among young adults. On the other hand, we find no evidence of an improvement in mental health or psychological well-being among the elderly at age 65 due to becoming eligible for Medicare. These results are robust to potential changes in risk-taking behavior and physical health at the same age cutoffs.
Keywords: I12; I13; I18; 330; affordable care act; dependent coverage; health insurance; medicare; mental health; psychological well-being